2019
DOI: 10.12968/jowc.2019.28.11.775
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic necrotising fasciitis of the breast: a case study with literature review

Abstract: Necrotising fasciitis is a rare infection of the skin and underlying soft tissue. It primarily involves the extremities and rarely the breast. Primary necrotising fasciitis of the breast in a non-lactating, healthy female is rarer still. The authors present the case report of a patient presenting with primary necrotising fasciitis of the breast after sustaining a penetrating injury. The patient was managed successfully with serial debridement and negative pressure wound therapy (NPWT). To our knowledge only 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Skin findings are much smaller than the actual extent of the disease because many dermal capillary beds must go through thrombosis before skin changes suggestive of necrosis can occur [7] . Based on the etiologic agents' necrotizing fasciitis can be classified into Four main categories, but the first two types are the most common: Type 1 necrotizing fasciitis is most commonly seen and tends to be poly-microbial infection including anaerobes, Type 2 which is caused by group A beta-hemolytic streptococci with or without staphylococci, Type 3 is caused by vibrio species and Type 4 which is caused by fulgal infection mainly candida, and it is usually associated with trauma [8] . NF can affect any part of the body, especially the trunk, lower and upper limbs, the perineum, and external genitalia (Fournier's gangrene) [4] , [6] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Skin findings are much smaller than the actual extent of the disease because many dermal capillary beds must go through thrombosis before skin changes suggestive of necrosis can occur [7] . Based on the etiologic agents' necrotizing fasciitis can be classified into Four main categories, but the first two types are the most common: Type 1 necrotizing fasciitis is most commonly seen and tends to be poly-microbial infection including anaerobes, Type 2 which is caused by group A beta-hemolytic streptococci with or without staphylococci, Type 3 is caused by vibrio species and Type 4 which is caused by fulgal infection mainly candida, and it is usually associated with trauma [8] . NF can affect any part of the body, especially the trunk, lower and upper limbs, the perineum, and external genitalia (Fournier's gangrene) [4] , [6] .…”
Section: Discussionmentioning
confidence: 99%
“…A score of greater than 8 gives greater than 75 % of probability of a diagnosis of NF. Based on the above the criteria, our patient had a score of 4 (random blood sugar of 200 mg/dl and anemia 10.7 mg/dl and the others parameters were normal except C-reactive protein which is not determined since it is not done in our hospital) [8] . However, if there is a high suspicious based history and physical examination, the patient should go straight to operative debridement regardless of the LRINEC score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Necrotizing fasciitis of the breast can be idiopathic [1,13] or secondary to other causes, i.e, following a needle core biopsy [14,15], elective total or partial mastectomy [7,[16][17][18][19], human bites [15], penetrating injury [20], anticoagulation therapy [21][22][23], topical belladonna application [24], in patients with puerperal sepsis [25], and breast tumors with mammary infarcts in pregnant patients [26,27]. Our literature search revealed that trauma, small trivial wounds, or even minor scratches can cause necrotizing fasciitis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Although breast conservation is possible in most cases [ 11 , 30 ], early radical mastectomy can be life-saving in severe cases of necrotizing fasciitis [ 2 , 8 , 9 ], as was the case with our patient. If the defect is large and not amenable to primary closure, a vacuum-assisted closure (VAC) dressing can assist in the closure of the wound [ 20 ] but may often require a split-thickness skin graft to cover the defect [ 34 ] or other advanced reconstructive procedures [ 4 , 9 ].…”
Section: Discussionmentioning
confidence: 99%